METODE LATIHAN KEKUATAN TANGAN TERHADAP PENINGKATAN PASSING ATAS PADA EKSTRAKURIKULER BOLA VOLI PUTRA DI SMP NEGERI 5 KUNINGAN - Rifa’i Hilmi; Dani Nurdiansyah (Journal of Physical Education and Sport Science, 2019)
Hand Strength Training Methods Against Passing Over in Men's Volleyball Extracurricular at SMP Negeri 5 Kuningan in 2020 ". The amount between after doing the hand strength training method and before doing the hand strength training method on extracurricular. This study used an experimental research method with the population of this study were 16 athletes. Determination of the sample using a total sampling technique with all athletes to be the research subjects. The instrument used to obtain information about volleyball passing skills in volleyball games), ", before doing the hand strength training method, the normality test value was 0.742> 0.05 and the homogeneity test amounted to 0.798> 0.05 while after doing the training method Hand strength obtained normality test values ​​amounting to 0.783> 0.05 and the homogeneity test amounting to 0.823> 0.05.